Menilik Perjanjian Kerja Sebagai Perwujudan Terpenuhinya Hak dan Kewajiban Para Pihak - Julastrid Jelita Katili (Syntax Idea, 2044)
One of the bases in the employment relationship which gives rise to an engagement or legal relationship for the parties is the employment agreement which gives rise to the rights and obligations of the parties. The existence of work agreements regulated in Law Number 13 of 2003 concerning Employment is expected to realize the rights and obligations of the parties fairly, however in practice this has not been fully fulfilled. The principles of contract law must be fulfilled and in harmony with the principles contained in the employment agreement. These principles include the principle of freedom of contract, the principle of consensualism, the principle of legal certainty, the principle of good faith, the principle of personality, the principle of trust, the principle of legal equality, the principle of balance, the principle of legal certainty, the principle of morals, the principle of decency and the principle of protection. All of these principles are related and cannot be separated.